Pengembangan Konstruksi Metodologi Hukum Islam bagi Perubahan Masyarakat Indonesia - Ummah, Karimatul (Jurnal Hukum IUS QUIA IUSTUM, 2016)
In facing the problem of more and more complex life, the Islamic law must be dynamic and actualin order that its role can be maximized both as a guidance controller of the change of society. In this condition, the effort of developing the methodological construction of Islamic Law is a must, but it uses the frame of its function.